SVPWM technique for 3-ph 6-switch and 3-ph 4-switch inverters - a comparison - Anitha, Golkonda; Krishnaveni, Kondreddi; Yesuratnam, Guduri (Institute of Advanced Engineering and Science, 2024)
A novel 3-ph 4-switch inverter (TPFSI) is described in this study to reduce the inverter's size, complexity, cost, and losses during the conduction and switching process. This TPFS inverter is based on the principle of similarity of a 3-ph 6-switch inverter (TPSSI) where αβ plane is separated into six sectors to form the required reference voltage space vector. It has been demonstrated that TPFS inverters are more efficient than TPSS inverters while operating with different loads. A mathematical concept for the space vector pulse width modulation (SVPWM) technique has been developed for TPFSI by using Clarke's transformation. In this paper, a TPFS inverter model is designed to reduce the harmonic content in the output voltage and current responses when connected to different loads. The suggested modulation method enhances the output voltage/current response, resulting in usually balanced waveforms and reduced harmonic distortion. MATLAB/Simulink software is utilized to analyze the output response of both inverters.